Sistem Informasi Penyewaan Perumahan Mutiara Simpang Mangga Berbasis Web - Zunaibah Siregar; Putri Erwina; Musthafa Haris Munandar (Universitas Labuhanbatu, 2021)
Along with the rapid development of the internet in recent years is very influential on the lives of millions of people. The Internet provides convenience in accessing very valuable information at a low cost and does not depend on location. With the development of internet users, then this can be used by entrepreneurs to market their products through the internet. Therefore in this study will be developed a program, so as to support the process of marketing and sales transactions through the internet. For software development methods, using structured methods, namely Data Flow Diagrams and Entity Relationship diagrams. For programming language using PHP while for database using MySQL / XAMPP. The method used in building this application is the waterfall method, proposing an approach to systematic and sequential software development that starts at the level and advances the system throughout analysis, design, code, testing and maintenance.